Where next for research on teaching assistants: the case for an international response. Issue 2 (15th March 2021) - Webster, Rob; De Boer, Anke A.
ABSTRACT: In this paper, the guest editors consider the direction of research on teaching assistants (TAs), and how academics can elevate the field within the spheres of education and the social sciences. We begin by unpicking, and endorsing, Giangreco's idea of applying the 'Maslow's Hammer test' (expressed in this special issue) to manuscripts about studies of TAs and inclusion to journal editorship and peer review processes. The purpose of the test is to address the disproportionate attention paid by researchers to a set of narrow and recurring interests, and to open up new lines of inquiry and discussions about the innovative methodological approaches required to operationalise them. Secondly, we describe a persistent and urgent research gap: the shortage of international data on TAs. Given the pre-eminence of TA deployment as a means to facilitate access to and participation in mainstream education for pupils with special educational needs, we argue that the continued lack of large-scale data on TAs' characteristics, experiences, practices and impact poses a risk to advancing the global inclusion agenda. Finally, we make a call for expressions of interest in establishing an international research network to help expand, empower and raise the esteem the field of scholarship on TAs.